Douglas Huebler and the Photographic Document. (1st October 2016) - Berger, Christian
Abstract : This article discusses the concepts of document and documentation in Douglas Huebler's (1924–1997) work of the late 1960s in order to assess the role of referentiality and subject matter within conceptualism more broadly. It examines the complex form and function of documents in his Location Pieces and establishes documentation as the zone of encounter between an artistic concept, proposal, or system, and the outside world. Focusing on the essential role of photographic images in his pieces affords new analysis of Huebler's practice. Central to that practice was the tension between the photograph as an allegedly neutral document – an idea deeply rooted in the history of photographic discourse – and its critical as well as aesthetic potential.